The challenge of the confiscated companies. Between local systems and entrepreneurial models (Rivista di Studi e Ricerche sulla criminalità organizzata, 2017)
This article was originated by an european research in which Milan University’s Department of Social and Political Sciences took part. It faces an advanced theme to fight the mafia crime: the confiscated firms and the possibility to convert them into legal economy. Moving from thet results of a survey about ten business cases, the article tries to focus the numerosity and complexity of the actors conditioning the chances of every single project of legal conversion, emphasizing the specifities of the external economies and diseconomies. Besides, it tries to bring the researchers’ results into a wider theoretical framework, revisiting some classic questions of the economic sociology: the local systems, the social approval of the entrepreneurship, and the so-called collective entrepreneur, of which the article proposes a new, original figure.Keywords: Confiscated assets, Mafia-like organizations, local systems, social approval, collective entrepreneur